Playerunknown's battlegrounds (PUBG Corporation, 2018)
"Playerunknown's Battlegrounds is the definitive battle royale shooter, pitting 100 players against each other in a struggle for survival. Starting with nothing, players drop into battle and must fight to stay alive while searching for weapons and supplies as the map shrinks and the combat intensifies. Spanning a variety of thrilling and immersive environments that uniquely change the style of gameplay and survival tactics playerunknown's Battlegrounds is not just a game - this is battle royale. Xbox live Gold required to play (sold separately)."--Amazon.

Star wars battlefront II (Electronic Arts Inc, 2017)
"Play as heroes from all three eras of Star Wars in massive battles across iconic locations, and take part in a ... single-player story as Iden Versio fights to avenge the Emperor."--EA website.